DAMPAK AUSTRALIA-INDONESIA FACILITY FOR DISASTER REDUCTION FASE 1 PERIODE 2009-2015 TERHADAP KAPASITAS TEKNOLOGI INDONESIA DALAM MENANGGULANGI KEJADIAN TSUNAMI - Nicolas Budiasih, (2020)
Tsunami has become the main hazard that threatens areas bordering the sea since forever, or at least since the oldest recorded tsunami in 479 BC. Indonesia, as an archipelago nation, is no exception. The absence of an early warning when a tsunami wave struck Aceh Province in 2004 is one of the many proofs that shows the lack of Indonesian technological capacity in tackling tsunami hazard. As a cooperation initiated by BNPB's Deputy for Prevention and Preparedness, AIFDR phase 1 was agreed by both parties, namely BNPB and AusAID, to enhance Indonesia's local and national capacity in the field of disaster management. Encouraged by Indonesia's national interests, which can be seen from a development perspective, as well as Australia's, which can be seen from security, trade, and disaster management perspectives, this facility was able to run for 7 years until the end of its operation period. With qualitative approach and case study method, the author aim to explore this case study and elaborate the results based on the author's interpretation. Congruence procedure and process-tracing methods the writer used is utilized to prove the argument the author has. The results of this study shows that AIFDR phase 1 has succeeded in increasing the capacity of Indonesian technology in tackling tsunami hazard, specifically in detecting, monitoring, and estimating their impact, which is shown through an increase in the number of tsunami management technologies that Indonesia has for the period of 2016-2019.